2007
DOI: 10.1038/sj.bjc.6603822
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle and socio-demographic factors associated with high-risk HPV infection in UK women

Abstract: The world age-standardised prevalence of high-risk HPV (hrHPV) infection among 5038 UK women aged 20 -59 years, with a lowgrade smear during 1999 -2002, assessed for eligibility for TOMBOLA (Trial Of Management of Borderline and Other Low-grade Abnormal smears) was 34.2%. High-risk HPV prevalence decreased with increasing age, from 61% at ages 20 -24 years to 14 -15% in those over 50 years. The age-standardised prevalence was 15.1, 30.7 and 52.7%, respectively, in women with a current normal, borderline nuclea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
32
3
9

Year Published

2008
2008
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 43 publications
7
32
3
9
Order By: Relevance
“…The result showed a difference of opinion while comparing to studies done by others (Cite Table2).The overall prevalence of HPV was 42.5%in the US (Susan Hariri et al,. 2011) [16] , 13.3% in southeast China (Ye et al 2010) [17] , 15.1% in the UK (Cotton et al 2007) [18] , and 22.7% in Greek population (PetroulaStamatakiet al,2010) [19] . The evaluation of our study showed a lower HPV prevalence in cervical smears compared with the study done by Laikangbam P et al, (2007) [20] in Sikkim and Kulkarni SS et al, (2011) [21] in Karnataka and in Andhra Pradesh (Pavaniet al,.2005) [24] but similar results were found by study done in Uttar Pradesh (Srivastava S et al,2012) [22] and in Eastern India (Dutta S et al,.…”
Section: ) the Statistical Analysismentioning
confidence: 99%
“…The result showed a difference of opinion while comparing to studies done by others (Cite Table2).The overall prevalence of HPV was 42.5%in the US (Susan Hariri et al,. 2011) [16] , 13.3% in southeast China (Ye et al 2010) [17] , 15.1% in the UK (Cotton et al 2007) [18] , and 22.7% in Greek population (PetroulaStamatakiet al,2010) [19] . The evaluation of our study showed a lower HPV prevalence in cervical smears compared with the study done by Laikangbam P et al, (2007) [20] in Sikkim and Kulkarni SS et al, (2011) [21] in Karnataka and in Andhra Pradesh (Pavaniet al,.2005) [24] but similar results were found by study done in Uttar Pradesh (Srivastava S et al,2012) [22] and in Eastern India (Dutta S et al,.…”
Section: ) the Statistical Analysismentioning
confidence: 99%
“…24 The generalisability of the findings of ALTS is uncertain, particularly to populations in which the prevalence of infection with HPV in women with mild dyskaryosis or LSIL is lower, 4 as reported in the UK. [25][26][27] In a Canadian trial in women with ASCUS or LSIL, addition of HPV testing to repeat cytology resulted in higher sensitivity for detection of CIN2 or worse, but with a substantial loss of specificity. 28 These findings may be highly context dependent, influenced by the relation between cytology interpretations and HPV test result, 29 different grading systems for cytological abnormalities, the character-istics of the women participating in screening, and the prevalence of HPV in screened women.…”
Section: Introductionmentioning
confidence: 99%
“…High-risk HPVs are also present in normal, benign hyperplastic and malignant prostate tissues (Zambrano et al, 2002). The prevalence of high-risk HPVs in females varies between populations and dramatically so between age groups, with the prevalence in near normal cervical smears from UK women 61% at ages 20-24 decreasing to 14-15% in those over 50 years (Cotton et al, 2007).…”
mentioning
confidence: 99%